2021
DOI: 10.1038/s12276-021-00565-3
|View full text |Cite
|
Sign up to set email alerts
|

Posthypoxic behavioral impairment and mortality of Drosophila melanogaster are associated with high temperatures, enhanced predeath activity and oxidative stress

Abstract: Hypoxia is an underlying pathophysiological condition of a variety of devastating diseases, including acute ischemic stroke (AIS). We are faced with limited therapeutic options for AIS patients, and even after successful restoration of cerebral blood flow, the poststroke mortality is still high. More basic research is needed to explain mortality after reperfusion and to develop adjunct neuroprotective therapies. Drosophila melanogaster (D.m.) is a suitable model to analyze hypoxia; however, little is known abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 40 publications
(24 reference statements)
2
19
0
Order By: Relevance
“…As previously described [45] hypoxia was induced with nitrogen (N 2 ) in a selfconstructed hypoxia chamber, consisting of a heated water chamber, gas-flow regulator, humidifier, and an airtight acrylic glass compartment with a stainless-steel bottom plate and lid (Figure 1a). The chamber enables control and monitoring of oxygen levels (Greisinger GOX 100 T O 2 -Sensor, Greisinger, Regenstauf, Germany), humidity, temperature (Habor Thermo-Hygrometer, Habor, Deggenhausertal, Germany), and pressure (Fluke 700RG06 100 PSIG pressure gauge, Fluke, Glottertal, Germany).…”
Section: Hypoxia Chambermentioning
confidence: 99%
See 2 more Smart Citations
“…As previously described [45] hypoxia was induced with nitrogen (N 2 ) in a selfconstructed hypoxia chamber, consisting of a heated water chamber, gas-flow regulator, humidifier, and an airtight acrylic glass compartment with a stainless-steel bottom plate and lid (Figure 1a). The chamber enables control and monitoring of oxygen levels (Greisinger GOX 100 T O 2 -Sensor, Greisinger, Regenstauf, Germany), humidity, temperature (Habor Thermo-Hygrometer, Habor, Deggenhausertal, Germany), and pressure (Fluke 700RG06 100 PSIG pressure gauge, Fluke, Glottertal, Germany).…”
Section: Hypoxia Chambermentioning
confidence: 99%
“…The activity of each fly was assessed as previously reported [45]. After hypoxia, each fly was transferred into the Drosophila Activity Monitoring system (Model DAM2, Trikinetics Inc., Waltham, MA, USA).…”
Section: Drosophila Activity Monitoring Assay (Dam)mentioning
confidence: 99%
See 1 more Smart Citation
“…The Drosophila functional homolog of HIF-1α is Similar [ 52 ]. Hypoxia-induced activation of Similar leads to over branching caused by elevated Drosophila FGF, Branchless (Bnl) [ 53 ] as well as increased ROS levels, similar to what was observed in COPD patients [ 54 ].…”
Section: Drosophila Trachea As a Model To Reveal Underlying Mechanisms Of Tube Morphogenesismentioning
confidence: 99%
“…Although adult fruit flies normally do not live at extremely low oxygen tensions, it has been shown that D. melanogaster effectively responds to variations in oxygen levels ( Zhao and Haddad, 2011 ). However, differently from mammals, fruit flies can tolerate short hypoxic or even anoxic treatments without apparent injury ( Zhao and Haddad, 2011 ; Azad and Haddad, 2009 ; Azad et al, 2009 ; Habib et al, 2021 ). Considering these features, the D. melanogaster organism is an ideal system to investigate the hypoxic response at its early stages, before the onset of major and irreversible damages to the organism.…”
Section: Introductionmentioning
confidence: 99%